Photoluminescence of gallium antimonide (GaSb) crystals doped with selenium (Se) and tellurium (Te) - Kusherbayeva, Maikul; Yegemberdiyeva, Sofia; Kushkimbayeva, Bibara; Keikimanova, Meruert (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
Abstract. This paper provides a brief overview of main works, dedicated to the study of photoluminescence in gallium antimonide crystals, as well as the features of the band structure and classification of impurity states. Photoluminescence of gallium antimonide doped with selenium and tellurium in the concentration range is presented (. ) for selenium and tellurium respectively. It is shown that GaSb photoluminescence is determined by changes from the conduction band to the second ionized state of the double natural acceptor. The shape and position of the maximum of the emission lines is determined by the Coulomb potential of the impurity, additional minima of the conduction band and resonant impurity states associated with them. It was revealed that the difference in the photoluminescence spectra of gallium antimonide crystals containing different donor impurities (selenium, tellurium) is due to the influence of resonant impurity levels associated with the L-minima of the conduction band. Theoretical calculations of the shape of GaSb photoluminescence spectra were performed. The position of the peak and the short-wavelength wing of the emission lines are essentially determined by the position of the Fermi level, which is due to the sharp increase in barrier transparency with increasing electron energy. The practical significance of the results in this article is also related to the widespread use of optical and photoluminescence phenomena in various types of semiconductor devices.